A liquid chromatography‐mass spectrometry untargeted urinary metabonomics combined with quantitative analysis of seven amino acids biomarkers on yaobitong capsule in the intervention of rheumatoid arthritis rats. Issue 23 (17th October 2022) - Zhang, Jing; Lu, Qing; Xin, Ling; Lou, Yanwei; Xiao, Wei; Wang, Zhenzhong; Zhao, Longshan; Xiong, Zhili
Abstract : Yaobitong capsule is a compound preparation of traditional Chinese medicine that has been widely applied in disease treatment. To insight into the therapeutic effects of the yaobitong capsule on rheumatoid arthritis and its mechanisms, a liquid chromatography‐mass spectrometry untargeted urine metabolomics method was established and validated, combined with the quantitative analysis of seven potential amino acid biomarkers in rat urine. The results showed that 35 potential biomarkers were found in untargeted metabonomics, which was related to amino acid metabolism, lipid metabolism, energy metabolism, and purine metabolism. Moreover, seven amino acid biomarkers, including proline, methionine, glutamic acid, histidine, lysine, cysteine, and glutamine, were further separated and quantified in multiple‐reaction monitoring with a positive ionization mode. Then the linearity, standard curves, accuracy, precision, limit of quantitation, recovery, stability, carryover, and matrix effect of the quantitative method were examined. Finally, the validated method was successfully applied to investigate the urine samples of the control group, adjuvant‐induced rheumatoid arthritis model group, yaobitong capsule‐treatment group, and positive control group in rats. The contents of seven amino acids in different groups showed significant differences. Consequently, our findings revealed that the yaobitong capsule exerted therapeutic effects on rheumatoid arthritis rats by maintaining amino acid homeostasis.